Examination of risk factors for discontinuation of follow‐up care in patients with head and neck cancer. (12th June 2022) - Howren, M. Bryant; Christensen, Alan J.; Pagedar, Nitin A.
Abstract: Background: Little research has examined discontinuation of follow‐up care in patients with head and neck cancer. This exploratory study sought to examine key demographic, disease, and behavioral factors as possible correlates of discontinuation ( N = 512). Methods: Cross‐sectional study examined correlates of discontinuation of follow‐up care within 1 year. The primary outcome was defined as a disease‐free survivor not returning to cancer clinic for two consecutive follow‐up appointments within the first year of care and not reentering oncologic care at any point thereafter. Demographic, disease, and behavioral factors were examined using multivariable logistic regression. Results: One hundred twenty‐six (24.6%) patients discontinued by 12‐month follow‐up. Being unmarried (OR = 1.28, 95% CI = 1.01–1.63, p = 0.041) and having elevated depressive symptomatology (OR = 1.04, 95% CI = 1.01–1.07, p = 0.034) were significantly associated with discontinuation. Receipt of a single (vs. multimodal) treatment approached significance (OR = 1.71, 95% CI = 0.96–3.07, p = 0.071). Conclusion: Approximately one quarter of patients disengaged from important follow‐up care within 1 year. Lack of social support, depressive symptomatology, and single treatment modality may be important correlates of discontinuation of care in patients with head and neck cancer. Additional studies of this outcome are needed. Improved understanding of correlates associated with discontinuation could facilitate the identification of at‐risk patients and further development of interventions to keep patients engaged at a crucial time in the survivorship care trajectory. Abstract : This exploratory study utilized data from a longitudinal study of head and neck cancer outcomes (N=512) to examine discontinuation of follow‐up care within one year and found that approximately one quarter disengaged from care. Multivariable logistic regression was used to examine correlates of discontinuation with lack of social support, depressive symptomatology, and single treatment modality possibly associated with this behavior.